Cross-linked electrospun cartilage acellular matrix/poly(caprolactone-co-lactide-co-glycolide) nanofiber as an antiadhesive barrier - Lee, Jin Woo; Park, Joon Yeong; Park, Seung Hun; Kim, Min Ju; Song, Bo Ram; Yun, Hee Woong; Kang, Tae Woong; Choi, Hak Soo; Kim, Young Jick; Min, Byoung Hyun; Kim, Moon Suk (Acta Biomaterialia, 2018)
In this work, we chose cartilage acellular matrix (CAM) as a promising antiadhesive material because CAM effectively inhibits the formation of blood vessels, and we used electrospinning to prepare antiadhesive barriers. Additionally, we synthesized N-hydroxysuccinimide (NHS)-poly(caprolactone-co-lactide-co-glycolide)-NHS (MP) copolymers (to tune degradation) as a cross-linking agent for CAM. This is the first report on the development of electrospun cross-linked (Cx) CAM/MP (CA/P) nanofiber (NF) (Cx-CA/P-NF) with a tunable degradation period as an antiadhesive barrier. Compared with the CA/P-NF before cross-linking, the electrospun Cx-CA/P-NF after cross-linking showed different biodegradation. Cx-CA/P-NF significantly inhibited the in vitro attachment and proliferation of human umbilical vein endothelial cells (HUVECs), as confirmed by an MTT assay and scanning electron microscopy images. Cx-CA/P-NFs implanted between a surgically damaged peritoneal wall and cecum gradually degraded in 7 days; this process was monitored by NIR imaging. The in vivo evaluation of the anti–tissue adhesive effect of Cx-CA/P-NFs revealed little adhesion, few blood vessels, and negligible inflammation at 7 days determined by hematoxylin and eosin staining. ED1 staining of Cx-CA/P-NFs showed infiltration of few macrophages because of the inflammatory response to the Cx-CA/P-NF as compared with an untreated injury model. Additionally, Cx-CA/P-NFs significantly suppressed the formation of blood vessels between the peritoneal wall and cecum, according to CD31 staining. Overall, Cx-CA/P-NFs yielded little adhesion, infiltration by macrophages, or formation of blood vessels in a postoperative antiadhesion assay. Thus, it is reasonable to conclude that the Cx-CA/P-NF designed herein successfully works as an antiadhesive barrier with a tunable degradation period. Statement of Significance: The cartilage acellular matrix (CAM) can inhibit the formation of fibrous tissue bridges and blood vessels between the tissue at an injured site and the surrounding healthy tissues. However, CAM has not been rigorously investigated as an antiadhesive barrier. In this manuscript, the cross-linked CAM nanofiber (Cx-CA/P-NF) designed herein successfully works as an antiadhesive barrier. Cx-CA/P-NFs yielded little adhesion, infiltration by macrophages, or formation of blood vessels in a postoperative antiadhesion assay. Moreover, we demonstrated the suitable properties of Cx-CA/P-NF such as easy cross-linking by maintaining the antiadhesive properties, controllable biodegradation, and in vivo antiadhesive effect of Cx-CA/P-NF.
Keywords: Acellular matrices; Anti-adhesive; Antiadhesive barrier; Cartilage acellular matrix; Cross linking; Electrospuns; Glycolide; Lactides; N-hydroxysuccinimide; Poly(-caprolactone); Animals; Extracellular Matrix; Human Umbilical Vein Endothelial Cells; Humans; Nanofibers; Polyesters; Rats; Rats, Sprague-Dawley; Tissue Adhesions; Antiadhesive barrier; Cartilage acellular matrix; Cross-linking; Degradation; Polyester